2019
DOI: 10.33403/rigeo.510360
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Dyslexic and Non-Dyslexic Students in the Performance of Spatial and Geographical Thinking

Abstract: Dyslexia is a specific form of learning disability which comes along with diverse difficulties, both in learning, social and emotional fields. It obstructs the development of the individual at all levels of education. This research investigates students' spatial and geographical thinking and whether there is a differentiation of these abilities between dyslexic and non-dyslexic ones. For this purpose, 50 questionnaires were distributed to 25 dyslexic and 25 non-dyslexic students aged 14 using opportunity sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In this way, we could choose teaching approaches that would develop this different learning ability of dyslexic students (Passadelli & Klonari, 2018). Therefore, teachers need to be supportive and adapt their teaching based on the skills and deficits of their students (Klonari & Passadelli, 2019b). Consequently, it is necessary to apply alternative teaching strategies that could be based on new technologies to provide effective teaching and learning for all students (Abdurrahman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, we could choose teaching approaches that would develop this different learning ability of dyslexic students (Passadelli & Klonari, 2018). Therefore, teachers need to be supportive and adapt their teaching based on the skills and deficits of their students (Klonari & Passadelli, 2019b). Consequently, it is necessary to apply alternative teaching strategies that could be based on new technologies to provide effective teaching and learning for all students (Abdurrahman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Since spatial science is directly connected with Geography, the Geography teachers should teach spatial science with an interactive way in order students to develop it. Klonari & Passadelli, (2019b) stated that although all students face difficulties in spatial thinking, the issue for dyslexic students is more acute. Dyslexia is a learning disability that affects various areas of academic performance .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is an area that needs further investigation. Now, in Greece although the Secondary Education Curriculum includes the development of spatial skills, in pilot research in 2019 we found that most students face problems with spatial thinking and, especially, students with dyslexia (Klonari and Passadelli, 2019). So, this research aimed to investigate spatial abilities of a larger sample of students to draw more accurate conclusions that will help a wider educational community to better handle students' spatial weaknesses.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers report that dyslexia is created by four causes: perceptual deficits [17][18][19][20][21], memory deficits [22,23], language processing deficits [7], and visual processing deficits [24][25][26]. Dyslexia does not only affect reading and writing but it has also been proved to cause topographic disorders and orientation problems [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%